2020
DOI: 10.3390/ma13071676
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Antimicrobial Activity of Non-Covalently Dispersed Carbon Nanotubes

Abstract: Microorganisms have begun to develop resistance because of inappropriate and extensive use of antibiotics in the hospital setting. Therefore, it seems to be necessary to find a way to tackle these pathogens by developing new and effective antimicrobial agents. Carbon nanotubes (CNTs) have attracted growing attention because of their remarkable mechanical strength, electrical properties, and chemical and thermal stability for their potential applications in the field of biomedical as therapeutic and diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Representative CLSM images of the E. coli CECT 434 GFP biofilms developed on different surfaces (Figure 6) clearly show an effect of the BM treatment on biof Results show a further decrease in the number of culturable cells for the ball-milled samples of around 24% when compared to the same loading (3 wt%) of CNT-O. This result suggests that BM treatment increases CNT's ability to disperse in the PDMS matrix, inducing morphological changes in the CNT/PDMS composites [45], which may increase the CNT surface contact with the microbial cells, leading to cell death [44]. Moreover, the effect of ball-milled CNTs on the reduction of E. coli adhesion and its association with the degree of dispersion of CNTs were already demonstrated [24].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Representative CLSM images of the E. coli CECT 434 GFP biofilms developed on different surfaces (Figure 6) clearly show an effect of the BM treatment on biof Results show a further decrease in the number of culturable cells for the ball-milled samples of around 24% when compared to the same loading (3 wt%) of CNT-O. This result suggests that BM treatment increases CNT's ability to disperse in the PDMS matrix, inducing morphological changes in the CNT/PDMS composites [45], which may increase the CNT surface contact with the microbial cells, leading to cell death [44]. Moreover, the effect of ball-milled CNTs on the reduction of E. coli adhesion and its association with the degree of dispersion of CNTs were already demonstrated [24].…”
Section: Discussionmentioning
confidence: 88%
“…However, only the surface with 3 wt% CNT-O loading presented a statistically significant reduction of cell culturability (p < 0.001), being the most promising surface for the inhibition of E. coli biofilms. The lower antimicrobial activity of 4 and 5 wt% CNT-O/PDMS surfaces may be justified by the decrease of CNTs dispersion degree imposed by increased loading, once the CNTs antimicrobial activity depends on their dispersion state [44]. Since no major differences were observed in the total cell number (Figure 4b), it is possible to assume that this decrease in cell culturability is a consequence of the antimicrobial activity of CNT-O/PDMS composites (an anti-adhesive activity would lead to a higher decrease in the total cell number).…”
Section: Antibiofilm Assaysmentioning
confidence: 99%
“…Some studies have identified oxidative stress (producing bacterial membrane damage) as one of the possible causes of the antimicrobial properties of CNTs [30][31][32][33][34]. However, recent studies have shown that the mechanical interaction of carbon-based nanomaterials with bacteria, and not oxidative stress, is the main antimicrobial activity of these compounds [35][36][37][38][39]. In particular, the first evidence of the strong antimicrobial activity of CNTs was obtained by treatment of Escherichia coli with SWCNTs, which caused severe membrane damage and bacterial death [40].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of these properties, they show a wide range of applications. For example, they have been used in electronics, polymer composites, energy storage materials, catalysis, gas storage materials, sensors, environment and biomedicine [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. These applications are limited due to a low and poor solubility in solution because of the existence of strong Van der Waals forces and π-π stacking interactions among the tubes, which provoke their agglomeration into ropes and/or bundles [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…They will also shed new light onto the difference between the adsorption of ionic surfactants at the CNT surfaces and the dispersion of these nanostructures by these ionic surfactants. Understanding the driving forces of both processes is important in relation to the wide range of applications of CNTs in which a good dispersion of the carbon nanotubes is essential [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%